Lead Tungstate /Zinc Oxide Heterostructure Nanocomposites: Luminescent Properties Under UV/Red Laser Excitation - Hosseinpour, Maryam; Abdoos, Hassan; Alamdari , Sanaz; Mirzaee, Omid; Menéndez, José Luis (Journal of Composites and Compounds, 2023)
Recently, there has been an increase in the ability to adjust the optical band gap and enhance the brightness of luminescence in nanophosphors that are utilized in light-emitting diodes and detectors. In this study, a dual oxide composite of erbium-doped lead tungstate/Ag-doped zinc oxide (PWO: Er/ZnO: Ag) heterostructures have been synthesized via a simple chemical method, and the structural and optical properties have been investigated. The effect of excitation wavelength (Landa Landaex) and excitation source was studied on the luminescence properties of the synthesized composite nanoparticle (NPs) at room temperature. Under UV illumination, doped nanocomposite demonstrated strong emission in the blue-green region compared to the pure sample at Landa Landaex=270-280 nm. XRD and EDX results confirmed the existence of PWO and ZnO in the dual composite structure along with the related components. The results demonstrate that mixed-dimensional heterostructures could be developed for high-performance optoelectronic devices using this method.